Construction on a new deep ice coring site at Dome Fuji Station -Operations carried out by the JARE-44 Dome Fuji overwintering team- - Takao Kameda; Ichio Obinata; Kyo Takahashi; Kenji Taniguchi; Okimasa Sugita; Koji Fujita; Takashi Kurisaki; Kei Nakano (National Institute of Polar Research, 2005)
Eight members of the 44th Japanese Antarctic Research Expedition (JARE-44) stayed at Dome Fuji Station (77°19′01″S, 39°42′11″E; 3810 m a.s.l.; ice thickness 3028±15 m; mean air temperature -54.4°C; lowest air temperature -79.7°C) from January 19, 2003 to January 25, 2004 for glaciological, meteorological, and upper atmospheric observations, and for construction at a new ice coring site for deep ice coring. The construction was a continuation of the activities of JARE-43; JARE-44 primarily carried out interior work at the ice coring site. The following works were carried out during the overwintering period and are described in this paper: retrieval of casing pipes from the borehole, enlargement of the borehole, insertion of casing pipes into the borehole, movement of the winch system from the old to the new ice coring sites (44.5 m apart), floor construction, construction and preparation of a 10 m depth pit for the rotating mast, construction of stairs between the old and the new ice coring sites, construction of working tables, assembling the mast and the small goliath crane, setting up a lifter, testing the winch system, setting the winch for the chip collector, cable replacement for deep ice coring, assembling of a deep ice core drill, adjustment of a rotating mast, enlargement of caves for ice core storage, and general electrical work in the new ice coring site. The total working time for the above operations was 593.5 person-days. Since the average working time was 6 h/day, the total working time was 3561 person-hours. Preparations for borehole temperature measurements in a 2503 m borehole and the ice coring operation that was mainly conducted by the JARE-45 team are briefly described.